ROLE OF FACILITIES ON VISITOR SATISFACTION IN GUNUNG BUNDER NATURAL TOURISM, BOGOR REGENCY - Yuviani Kusumawardhani (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2022)
Traveling activities can increase creativity, eliminate saturation, relaxation, shopping, doing business, learning about history, culture, and language from certain ethnicities, health, and spirituality. Indonesia is a country that has considerable natural tourism potential and has become an attraction for visitors from all over the world. Gunung Bunder Nature Tourism is one of the natural attractions located in Bogor Regency with pine tree attractions. But the management of tourist attractions is still carried out independently by the community, causing a lack of tourist facilities to be provided to visitors. This is behind this research to analyze the role of facilities on visitor satisfaction in Mount Bunder Natural Tourism.In research procedures, quantitative approaches with simple linear regression analysis tools are used. Nonprobability sampling with a purposive sample technique was utilized to collect data from as many as 100 people. The findings revealed that facility variables influence visitor happiness, implying that facilities have a role in visitor pleasure and that if the manager improves the facility, tourist contentment will rise. The findings of the determination coefficient test revealed that facilities had a 71.9 percent effect on visitor satisfaction, with the remaining 28.1 percent influenced by factors not addressed in this study.